Urban memory and the evolution of the urban environment - Testa, Charl Rudolph (School of Architecture, Planning and Geomatics, 2016)
An individual's connection to the world is facilitated by memory as it envelops every feature of human experience. In the absence of memory, meaning collapses. In architectural terms, if memory exists as the foundation upon which meaning is built, if a person is to find and experience meaning in their built environment, architecture must necessarily engage its temporality. The focus of this project is architecture's peculiar mnemonic capacity as it relates to memory and place. Associated themes are explored through theoretical, technological and design components. Included here are brief descriptions of the three components. The purpose of the technology and theory components was to test and develop my understanding of the dynamics of memory in the built environment and the implications of these dynamics for design and thought about architecture. Conclusions and discoveries then materialise in a design proposition.